Kepemimpinan Transformasional Kepala Desa Dalam Inovasi Pembangunan Desa Di Desa Sugihwaras Kecamatan Candi Kabupaten Sidoarjo - Maria Veronika Andarista; Arimurti Kriswibowo (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
The leadership of the village head has a strong influence in driving village development so that it achieves success. The village head's current leadership is required to realize the village's vision to become an independent and democratic village. Transformational leadership can anticipate better future conditions, so it is the right leadership model because it adapts to a changing environment. Therefore, transformational leadership is needed to achieve the village's vision and mission, and in 2021 won various awards at the local and provincial levels. Although village funds are limited, they can implement village development innovations, namely the Griya Sinau Digital program and digital-based services. This study aimed to discover how village heads' transformational leadership in village development innovations in Sugihwaras Village, Candi District, Sidoarjo Regency. The method used is descriptive qualitative with observation, interviews, and documentation. According to Bass and Avolio, the theory used is the theory of transformational leadership. The findings in this study are the realization of digital service innovations and Griya Sinau Digital in village development through the transformational leadership of the Sugihwaras Village Head, Candi District, Sidoarjo Regency.